PENGARUH OVERCONFIDENCE, ILLUSION OF CONTROL, ANCHORING, LOSS AVERSION PADA PENGAMBILAN KEPUTUSAN INVESTASI OLEH MAHASISWA UNISRI SEBAGAI INVESTOR PEMULA - Sigit Dwi Handoyo; Rispantyo Rispantyo; Bambang Widarno (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2020)
The main problem in this research is whether there is an influence of financial behavior overconfedence, illusion of control, loss aversion and anchoring that is owned by novice investors. The purpose of this study is to determine and test the effect of overconfidence, illusion of control, loss aversion and anchoring on decision making. This study uses survey methods and data collection techniques using purposive sampling method with a total of 100 respondents. Then analyzed using descriptive statistics and data analysis techniques used are multiple linear regression analysis. The results of this study indicate that overconfiedence, illusion of control, loss aversion and anchoring affect the investment decision making by novice investors in the University of Slamet Riyadi Surakarta.